The Influence of Interleukin-4 on Ligament Healing - Chamberlain, Connie S (2011)
Despite a complex cascade of cellular events to reconstruct the damaged extracellular matrix, ligament healing results in a mechanically inferior scarred ligament. During normal healing, granulation tissue expands into any residual normal ligamentous tissue (creeping substitution), resulting in a larger region of healing, greater mechanical compromise, and an inefficient repair process. To control creeping substitution and possibly enhance the repair process, the anti-inflammatory cytokine, interleukin-4 (IL-4) was administered to rats prior to and after rupture of their medial collateral ligaments. In vitro experiments demonstrated a time-dependent effect on fibroblast proliferation after interleukin-4 treatment. In vivo treatments with interleukin-4 (100 ng/ml i.v.) for 5 days resulted in decreased wound size and type III collagen and increased type I procollagen, indicating a more regenerative early healing in response to the interleukin-4 treatment. However, continued treatment of interleukin-4 to day 11 antagonized this early benefit and slowed healing. Together, these results suggest that interleukin-4 influences the macrophages and T-lymphocytes but also stimulates fibroblasts associated with the proliferative phase of healing in a dose-, cell-, and time-dependent manner. Although treatment significantly influenced healing in the first week after injury, interleukin-4 alone was unable to maintain this early regenerative response.